Ticagrelor with or without Aspirin in High-Risk Patients after PCI - Mehran, Roxana; Baber, Usman; Sharma, Samin K; Cohen, David J; Angiolillo, Dominick J; Briguori, Carlo; Cha, Jin Y; Collier, Timothy; Dangas, George; Dudek, Dariusz; Džavík, Vladimír; Escaned, Javier; et al. (The New England journal of medicine, 2019)
In this placebo-controlled trial, 7119 patients were randomly assigned at 3 months after PCI to either receive ticagrelor alone or continue dual therapy with ticagrelor plus aspirin. The trial evaluated bleeding and ischemic end points at 1 year.